2018
DOI: 10.1016/j.devcel.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Adhesive Forces through Src/FAK Drives Contact Inhibition of Locomotion in Neural Crest

Abstract: SummaryContact inhibition of locomotion is defined as the behavior of cells to cease migrating in their former direction after colliding with another cell. It has been implicated in multiple developmental processes and its absence has been linked to cancer invasion. Cellular forces are thought to govern this process; however, the exact role of traction through cell-matrix adhesions and tension through cell-cell adhesions during contact inhibition of locomotion remains unknown. Here we use neural crest cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 91 publications
3
39
0
Order By: Relevance
“…We previously showed that EphB2 activation of Sox2 results in the clustering of SCs but video analysis showed these clustered cells appeared to maintain CIL, as the cells appeared to be attempting to migrate away from the cluster 12 . This is consistent with the migration of SC cords during nerve regeneration, which would be predicted to require a force such as CIL to drive migration forward 18,21,23,24 . N-cadherin has been implicated in CIL in other cell types 21,22,25 , so we addressed whether N-cadherin was also required for the regulation of collective SC migration.…”
Section: N-cadherin Is Required For Contact Inhibition Of Locomotion supporting
confidence: 77%
See 1 more Smart Citation
“…We previously showed that EphB2 activation of Sox2 results in the clustering of SCs but video analysis showed these clustered cells appeared to maintain CIL, as the cells appeared to be attempting to migrate away from the cluster 12 . This is consistent with the migration of SC cords during nerve regeneration, which would be predicted to require a force such as CIL to drive migration forward 18,21,23,24 . N-cadherin has been implicated in CIL in other cell types 21,22,25 , so we addressed whether N-cadherin was also required for the regulation of collective SC migration.…”
Section: N-cadherin Is Required For Contact Inhibition Of Locomotion supporting
confidence: 77%
“…CIL can provide an outward force in collectively migrating cells [21][22][23] . To test if the Slit CIL signal is important for the collective migration of SCs, we performed a wound-healing assay with SCs knocked down for Slit2 and Slit3 and found that this was sufficient to decrease the collective migration of these cells ( Fig.…”
Section: Slit Is Required For the Efficient Collective Migration Of Smentioning
confidence: 99%
“…(B) Overexpression of C3GF rescued Crk/Crkl deficiency-induced inhibition of cell proliferation. Cell investigate precise mechanisms that underlie the abnormal cell contact behavior (Fig 2B-D), a recent study reported that normal CIL relies on Fak and Src for coordinated redistribution of cell-matrix contacts and intracellular force in frog neural crest cells (Roycroft et al, 2018). Because Crk and Crkl mediate signals partly from Fak and Src (Shin et al, 2004;Birge et al, 2009;Watanabe et al, 2009), it is plausible that Crk and/or Crkl are also required for traction force redistribution, a key mechanism for repulsive locomotion as an essential feature of mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of CiL for the migration of NC cells was demonstrated using Xenopus and zebrafish cephalic NC cells (Carmona-Fontaine et al 2008;Theveneau et al 2010;Mayor and Carmona-Fontaine 2010). Further evidence for CiL has been recently provided by Roycroft et al (2018), who showed how CiL could arise via the redistribution of adhesive forces through Src/FAK (steroid receptor coactivator and focal adhesion kinase). The existence and necessity of the opposite phenomenon, namely CoA, to ensure that the cells remain in a group, has been verified in Xenopus cephalic NC cells (Carmona-Fontaine et al 2011).…”
Section: Fixed Domainmentioning
confidence: 96%